Sosialisasi Kewirausahaan Prodi PPKn pada Generasi Muda Labuhanbatu - Agus Anjar; Yuniman Zebua; Gomal Juni Yanris Silaen (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2024)
This entrepreneurship socialization carries the theme of Young Generation, Generation of Work, attended by three speakers consisting of education, public transportation and culinary fields. This activity was held considering that entrepreneurship among the younger generation is not yet widely practiced but tends to be more in demand by adults. The purpose of this entrepreneurship socialization activity is to provide advice so that young people are bigger and have no doubts about entering the business world. The activity held in Rantauprapat was attended by 60 participants.